Paleoenvironment and diagenetic aspects of the limestone (Gboko Formation) around Igumale, Central Benue Trough, Nigeria: Evidence from petrography - Israel Etobro; O. I. Ejeh; Oghenerhoro Odedede (Ruhuna Journal of Science)
Limestone core samples from Igumale-1 and Igumale-2 wells, Central Benue Trough, Nigeria were petrographically studied in detail to determine their paleo-depositional environment and diagenetic history. Petrographic examination of the limestone shows that the limestone comprised monocrystalline quartz, ferroan calcite (3-15 %), peloids (3-20 %), ooids (7-10 %), micrite (33-48 %) and sparites (10-50 %). Fossil fragments consist of foraminifera and gastropods (17-57%), and suggest subtidal to shallow marine environment. Four sedimentary facies (oobiosparite, biosparite, biopelmicrite, and biomicrite) were recorded and characterised by moldic and vuggy porosity. This study has provided a petrographic synopsis of the limestone for further consideration and may impact both the exploration and development of the limestone deposit.